Learning Problems Among Children of Refugee Background: A Systematic Scoping Review. (1st June 2016) - Graham, H; Minhas, R
Abstract: BACKGROUND: Learning problems are common, affecting up to one in ten children, occurring within the dynamic, multidimensional context of family, school, community and broader sociocultural environment. Refugee children have, by definition, experienced forced migration, and multiple transitions, and ongoing socioeconomic and cultural challenges that may have cumulative risk factors for learning problems and educational disadvantage. OBJECTIVES: To review the prevalence and major determinants of learning problems in resettled refugee children and available evidence on their educational outcomes. DESIGN/METHODS: A scoping review using Arksey and O'Malley's framework for scoping studies was employed (a systematic search, selection, extraction, analysis and reporting strategy) to identify the prevalence, major determinants of learning problems and educational achievement in resettled refuge children. Relevant studies were identified from searches of MEDLINE, EMBASE, PubMed, CINAHL PsycInfo, and ERIC. Inclusion criteria were peer-reviewed articles in English addressing the prevalence and/or determinants of learning problems in refugee children. Two independent authors conducted abstract and full text article review. The data was extracted systematically and analysed using Arksey and O'Malley's descriptive analytical method for scoping studies. RESULTS: A total of 2002 studies were identified and 28 studies met the inclusion criteria to be included in the review. No information was available on the prevalence of specific learning issues, language disorders, or autism spectrum disorders. Included studies found refugee children to possess significant 'resource' factors that promote learning success and had similar academic outcomes compared to their native-born peers. Prevalence data were limited, with single studies informing most of the reported estimates. Eight studies examined the impact of trauma on learning identifying mental health issues, personal risk behaviours and lower school performance as key risk factors. Key resource factors were strong family ties, absence of racial discrimination, and school safety. CONCLUSION: This review provides prevalence estimates for learning problems in refugee children, and highlights key 'risk' and 'resource' factors. This review provides paediatricians recommendations on how best to identify learning strengths and challenges in refugee children, to better advocate for support in achieving academic success. This review advocates for a larger experimental based research measuring educational outcomes in refugee children. Further research is needed to better define the prevalence of learning problems among children of refugee background and to map out the learning progress longitudinally.